2010
DOI: 10.1016/j.gaitpost.2010.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Range of motion and repeatability of knee kinematics for 11 clinically relevant motor tasks

Abstract: Standard gait analysis reports knee joint rotations in the three anatomical planes without addressing their different levels of reliability. Most clinical studies also restrict analysis to knee flexion-extension, because knee abduction-adduction and axial rotation are small with respect to the corresponding amount of measurement artefact. This study analyses a set of 11 motor tasks, in order to identify those that are adequately repeatable and that can induce greater motion at the knee than walking. Ten volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 35 publications
1
17
0
1
Order By: Relevance
“…The knee's range of motion was under special consideration because of the frequency of injuries in sport activities. The repeatability of knee motion measurement turned out to be the lowest during squat and lung exercises when compared to eleven motor tasks [23]. In our study we analyzed the hip, the ankle and the knee joints and the pelvic and the spine motion, and we observed the highest repeatability during the two-leg squat and the forward bending in a sagittal plane.…”
Section: Forward Stepmentioning
confidence: 56%
“…The knee's range of motion was under special consideration because of the frequency of injuries in sport activities. The repeatability of knee motion measurement turned out to be the lowest during squat and lung exercises when compared to eleven motor tasks [23]. In our study we analyzed the hip, the ankle and the knee joints and the pelvic and the spine motion, and we observed the highest repeatability during the two-leg squat and the forward bending in a sagittal plane.…”
Section: Forward Stepmentioning
confidence: 56%
“…Starting from 0°, the knee flexion during walking is up to 65°, during the step descent is up to 68°, during the step ascent is up to 93°and for the squat is up to 120°. Each movement follows a standard kinematics characteristic for the analysed movement as also obtained from in vivo gait lab analyses (Desloovere et al 2010). To allow a following validation for contact forces outputs, these settings also match experimental tests performed in in vitro analyses on cadaver legs (Innocenti, Follador, et al 2009;Victor 2009;Delport et al 2013).…”
Section: Methods Modelsmentioning
confidence: 99%
“…Previous studies demonstrated that Mo-Cap for gait and motion analysis is remarkably accurate, and it contains both three-dimensional and temporal information in comparison to traditional methods for obtaining human mobility data. Adaptability and the customisation of such systems allow researchers and clinicians to focus their research specifically to the area that is of most interest to them, allowing the capturing of motion data related to selected MSK elements [34]. However, the majority of such systems require a large deployment footprint and multiple sensors positioned in the periphery in order to acquire any useful data, as depicted in Figure 3 below.…”
Section: Motion Capturementioning
confidence: 99%
“…Clinicians and researchers have begun to experiment and develop tools with such devices to assist motion-driven tasks [34,36,37]. A sufficient amount of interest has been an aid for rehabilitation purposes [37,38].…”
Section: Motion Capturing and Rehabilitation System Trendsmentioning
confidence: 99%